2015
DOI: 10.1128/jvi.03453-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dengue Virus NS4A and NS4B Protein Interaction

Abstract: Flavivirus replication is mediated by a membrane-associated replication complex where viral membrane proteins NS2A, NS2B, NS4A, and NS4B serve as the scaffold for the replication complex formation. Here, we used dengue virus serotype 2 (DENV-2) as a model to characterize viral NS4A-NS4B interaction. NS4A interacts with NS4B in virus-infected cells and in cells transiently expressing NS4A and NS4B in the absence of other viral proteins. Recombinant NS4A and NS4B proteins directly bind to each other with an esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 49 publications
3
112
0
Order By: Relevance
“…Since NS4B functions as an essential component of the viral replication complex, the inhibitors could function by interfering with protein-protein interactions during viral RNA synthesis. In line with this hypothesis, NS4B was recently reported to oligomerize itself (18) as well as to interact with NS1 (24), NS3 (25,26), and NS4A (27). Besides binding to viral proteins, NS4B is also expected to interact with host factors during viral replication.…”
Section: Discussionmentioning
confidence: 67%
“…Since NS4B functions as an essential component of the viral replication complex, the inhibitors could function by interfering with protein-protein interactions during viral RNA synthesis. In line with this hypothesis, NS4B was recently reported to oligomerize itself (18) as well as to interact with NS1 (24), NS3 (25,26), and NS4A (27). Besides binding to viral proteins, NS4B is also expected to interact with host factors during viral replication.…”
Section: Discussionmentioning
confidence: 67%
“…Zou et al showed that DENV NS4B forms a dimer or multimer but is not N glycosylated in virusinfected cells (15). Moreover, the same report showed a single species (15) and a later report of the same research group showed two species from recombinant NS4B protein expression which were assumed to be 2K-4B unprocessed and processed forms (8).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies reported that mutations in DENV NS4B adversely affect viral genome replication, strongly supporting the fact that NS4B is a component of the replication complex (4)(5)(6). Additionally, NS4B was found to interact with other NS proteins, such as NS3 and NS4A in DENV (7)(8)(9). Re-cently, NS4B was shown to have genetic and physical interactions with NS4A and NS1 in the related flaviviruses Japanese encephalitis virus (JEV) and West Nile virus (WNV), and these interactions were essential for viral genome replication (10,11).…”
mentioning
confidence: 68%
“…Residue K330 from the thumb region of the NS5 polymerase was shown to interact with the NS3 helicase (35). The accompanying paper by Zou et al (37) characterizes the NS4A and NS4B protein interaction, and further studies in the presence of RNA are now needed to clarify the detailed network of intermolecular contacts established between NS2B, NS4A, NS4B, and NS5 at various stages of RNA replication.…”
Section: Discussionmentioning
confidence: 99%